The Application and Outcome of Standard of Care Treatment in Elderly Women with Ovarian Cancer: A Literature Review over the Last 10 Years - Gibson, Steven J.; Fleming, Gini F.; Temkin, Sarah M.; Chase, Dana M. (Frontiers in Oncology, 2016)
The rising number and increasing longevity of the elderly population calls for improvements and potentially a more personalized approach to the treatment of cancer in this group. Elderly patients frequently present with a number of comorbidities, complicating surgery and chemotherapy tolerability. In the case of ovarian cancer, elderly women present with more advanced disease, making the issue of providing adequate treatment without significant morbidity critical. Most studies support the application of standard of care treatment to elderly women with ovarian cancer, yet it seems to be offered less frequently in the elderly. The objective of this review is to examine the application and outcome of standard of care treatment in elderly women with ovarian cancer. The aim is to ultimately improve the approach to treatment in this group.